Pemberdayaan Ibu Hamil Dengan Pemberian Asi Eksklusif Di Puskesmas Kassi-Kassi Kota Makassar - Imelda Iskandar; Sendy Pratiwi Rahmadhani; Satiani Dalle; Rika Asriani (Pusat Riset dan Inovasi Nasional, 2021)
Exclusive breastfeeding for babies in the first hour after birth and skin-to-skin contact between mother and baby are important factors in the beginning of the breastfeeding process where the baby will stay warm and the baby will get colostrum. However, the number of mothers who have breastfed their children in Indonesia is already high, namely 90%, but those who breastfeed exclusively for 6 months is still low at 20%. nutritional problems for toddlers and low achievement of exclusive breastfeeding as well as deaths under the age of 5, one of the causes of which is the lack of knowledge of mothers about the importance of giving exclusive breast milk, so it is necessary to carry out services aimed at increasing mothers' knowledge about exclusive breastfeeding in the Kassi-Kassi Health Center Working Area, Makassar City. The methods used in this activity are location survey, problem determination, formation of WhatsApp group classes, counseling and evaluation. The results of this activity. After carrying out online educational activities about exclusive breastfeeding, it was found that the activity increased pregnant women's knowledge about exclusive breastfeeding.